Organochlorine insecticide residues present in raw milk sold in the department córdoba, colombia (2012)
In this investigation organochlorine pesticide residues in raw milk from Dairy herds in the Cordoba department were determined. During the extraction procedure using a column of diatomaceous earth as eluting system a mixture of n-hexane-acetone-ethyl acetate (4:2:1), followed by 5% methanol in hexane. For the determination we used a gas Chromatograph Perkin Elmer, Autosystem XL with elec- tron capture detector, split less injection mode, a capillary column Rtx-5 30m, 0.25 mm id and 0.25 um film t and gt;ickness. B and gt;e recovery rate for certain pesticides were 7etween 88.5 and 96%, t and gt;e detection limits were defined 7etween 0.01 and 0.04 ng/g, relative standard deviations less t and gt;an 6%. Nn t and gt;e 6+ samples tested p, p’-DDT, a-HCH, ö-HCH, aldrin, dieldrin, endrin, heptachlor, heptachlor epoxide and y-c and gt;lordane were determined, esta7lis and gt;ing concentrations 7etween 2;.1 and 469.6 ng/g. B and gt;e freOuen- cies of occurrence ranged between 1.6 and 65.1% for heptachlor and p, p’-DDT, respectively. The older population that lives in the sub-regions: Middle Sinú, San Jorge and Savannas were exposed to high health risk associated with the concentration of a-HCH, aldrin and dieldrin in raw milk